UJI VARIASI KOSENTRASI DAYA HAMBAT METODE SUMURAN DAUN BINAHONG (Anredera cordifolia (Tenore) Steenis) PADA PERTUMBUHAN Candida albicans - Fadillah, Muhammad Arief; Amrita Aulia Sugiarto; Hamtini, Hamtini; Nurnida, Rossy (Politeknik Kesehatan Kementerian Kesehatan Banten, 2024)
Infections caused by Candida albicans are common health problems, especially among individuals with weakened immune systems. This study aims to evaluate the antifungal effectiveness of binahong leaf (Anredera cordifolia) decoction extract against the growth of Candida albicans using the well diffusion method. The extraction process was carried out by boiling the leaves using water as the solvent. The tested concentrations of the extract were 5%, 25%, 50%, 75%, and 100%. The tests were conducted using the well diffusion method on media inoculated with Candida albicans. The results showed that no inhibition zones formed at any tested concentrations of the binahong leaf extract (0 mm), indicating no antifungal activity against Candida albicans. Meanwhile, the positive control (ketoconazole) showed an average inhibition zone diameter of 60.25 mm. The inability to form inhibition zones is likely due to the degradation of active compounds during heating, the limitation of water in extracting non-polar compounds, and the poor diffusion of active compounds in the agar medium. Based on these findings, it can be concluded that binahong leaf extract obtained through boiling does not exhibit antifungal activity against Candida albicans using the well diffusion method.